STUDI KASUS PASIEN DENGAN CHRONIC KIDNEY DISEASE STAGE V ON HEMODIALYSIS - Hidayat, Wahyu; Patmawati, Try Ayu (Kelimutu Nursing Journal, 2023)
Chronic Kidney Disease (CKD) is a progressive disease without medication and high morbidity and mortality that generally occurs in the general adult population, especially in people with diabetes and hypertension. The purpose of this study was to describe a case study of patients with Chronic Kidney Disease Stage V on Hemodialysis. The research design uses case studies in a descriptive manner which aims to describe the nursing care carried out. The number of samples is 1 person who observed the data collection method of interviews, observation and physical examination. The presentation of the data was made by the researcher in the form of narrative text. This research was conducted on December 10, 2022. Data presentation can be accompanied by verbal expressions from the case study subjects which are the supporting data. The results of the study show the enforcement of the five nursing diagnoses based on the SDKI and the implementation of nursing actions based on SIKI. The conclusion in this study is that nursing care provided to patients and families refers to the SDKI, SLKI, and SIKI. As for his advice, further research is needed regarding the effectiveness of the interventions used which are based on the conditions of different patients.